Penatalaksanaan Hepatitis B pada Populasi Khusus - Filya A Hunou; Bradley J. Waleleng; Linda W. A. Rotty (Medical Scope Journal, 2022)
Abstract: Hepatitis B virus infection is still a big problem in public health worldwide. Hepatitis B contributes 80% to the cause of primary hepatocellular carcinoma and is also the second most common cause of cancer after smoking. In special populations, the management given is different from the management of hepatitis B patients who are not included in special populations. This is because in special populations there have been changes in the natural history of the disease, the risk of complications related to the liver, recommendations for VHB drugs to be used, and the duration of therapy. This study aimed to obtain the managemeny of hepatitis B in special populations. This was a literature review study using 10 literatures searched by using three data bases namely ProQuest, Pubmed, and ClinicalKey. Journals were selected based on inclusion and exclusion criteria. The results showed that the management of hepatitis B in special populations adjusted to the conditions of each population. In conclusion, the management of hepatitis B in special populations has a variety of treatments that are made according to the condition of each population, including the treatment strategy, drug selection, duration of administration, and monitoring needed during the therapy. Keywords: management of hepatitis B; special population   Abstrak: Infeksi virus hepatitis B merupakan masalah besar pada kesehatan masyarakat di dunia. Penyakit hepatitis B menjadi penyumbang sebesar 80% pada penyebab terjadinya karsinoma hepatoseluler primer dan juga menjadi penyebab kanker kedua terbanyak setelah rokok. Pada populasi khusus pentalakasanaan yang diberikan berbeda dari penatalaksanaan pada pasien hepatitis B yang tidak termasuk pada populasi khusus. Hal ini disebabkan pada populasi khusus telah terjadi perubahan riwayat alamiah penyakit, risiko komplikasi terkait hati, rekomendasi obat VHB yang akan digunakan, serta durasi terapi. Penelitian ini bertujuan untuk mengetahui penatalaksanaan hepatitis B pada populasi khusus. Jenis penelitian ialah suatu literature review dengan pencarian literatur menggunakan tiga data base yaitu ProQuest, Pubmed, dan ClinicalKey. Hasil penelitian mendapatkan bahwa kesepuluh literatur menjelaskan penatalaksanaan hepatitis B pada populasi khusus disesuaikan dengan kondisi masing-masing populasi. Simpulan penelitian ini ialah penatalaksanaan hepatitis B pada populasi khusus memiliki beragam penatalaksanaan yang dibuat menyesuaikan dengan kondisi masing-masing populasi, mulai dari strategi pengobatan yang diberikan, pemilihan obat, durasi pemberian, serta pemantauan yang perlu dilakukan dalam terapi. Kata kunci: penatalaksanaan hepatitis B; populasi khusus